Analyzing teachers' emotional labor levels according to some variables - Kartal, Secil Eda; Karakose, Turgut; Ozdemir, T. Yavuz; Yirci, Ramazan (Modern Journal Language Teaching Methods, 2017)
The purpose of this study is to examine emotional labor levels of teachers and the emotional labor dimensions of the scale with regards to the demographic characteristics of the participants. With this respect, the Emotional Labor Scale, developed by Diefendorff, Croyle, and Gosserand (2005) and adapted into Turkish by Basim and Begenirbas (2012), was used in the study. The study sample consists of a total of 277 teachers from 21 schools selected through the random sampling method. According to the data analysis results, teachers avoided role making and behaved as required by their profession. A significant difference was detected in favor of female teachers only for the scale's genuine emotions dimension with regards to the gender variable. According to the Kruskall Wallis-H test results, which was conducted according to the branch variable, with regards to the items of the deep role making dimension, there is a significant difference between classroom teachers and the science/math branch teachers in favor of classroom teachers and between science/math teachers and social science teachers in favor of the teachers from the social science branch. According to the Kruskall Wallis-H test results concerning the seniority variable, there is a significant difference only between the items of the genuine emotions dimension. Analysis results concerning the institution type variable show that as the age group of the students increase, the interaction created with students becomes more superficial.
Keywords: Emotional labor; teacher; public school; quantitative study